Modelos de prestação dos serviços de abastecimento de água e esgotamento sanitário: uma avaliação comparativa do desempenho no conjunto dos municípios brasileiros - Pedro Gasparini Barbosa Heller (2012)
This study presents a comparative assessment of the different institutional models for water supply and sanitation provision, in Brazil. In an encompassing way, the study develops a comparison of almost all Brazilian municipalities. For this comparison, the services weregrouped according to the following classification: (i) directly managed by the municipality; (ii) managed by municipal autarchy; (iii) private companies; (iv) regional companies. The research consists of four studies. The first refers to the comparison of institutional modelsof water supply, by a nonparametric analysis of variance and multiple comparisons, characterized by different performance indicators. In the second study, the same institutional models were compared, including multivariate analysis. The third study adopted the same design methodology followed by the first study, but in relation to sanitation services. Finally, in the fourth study, both services management models of water supply and sanitation are simultaneously compared also by nonparametric analysis of variance and multiple comparisons.The results point out important features of the management models of services evaluated. The group directly managed by the municipality stands with the worst performance for operational indicators, related to little capacity to invest in infrastructure and limited managementcapacity. The services managed by municipal autarchy distinguish itself with superior operational performance than the previous group, leading to reflection of the gain of a service to be decentralized of the direct administration. Private companies and regional companies aremarked by the best performance for water metering and non-payment, these services are based on a business logic. Regional companies are also responsible for lower values water supply main coverage, questioning the real potential of a service to be regionalized. On theother hand, this group is marked by the highest values of interception and treatment infrastructure levels of sanitation, observing weak performance of municipal services in this regard, although the group of municipal autarchy is responsible for higher values of sewerage network coverage.